Simulation of AC Package Train Roof Structure Strength using Software - Akbar Zulkarnain; Ajeng Tyas Damayanti; Muhammad Iqbal Yogapradana; Stefanus Sylvan Ryanto; Anggun Gilang Rupaka (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2022)
Modification of economic class coach originally is not designed to use package air conditioner. it was changed to use package air conditioner. It will be eliminated a few part of the train roof for air conditioner package holder. For ensure that the package air conditioner’s holder is safe, then it was analysed by strength analyses. Make remodeling the train roof and air conditioner holder structure with solidwork 2017. This structure use SS400 which has yield strength of 245 MPa., The mass of package air conditioner are 375 kg. The result of maximum stress is 31,866 MPa. Safety of factor’s result is 7,7. And then for the displacement’s value is 1173 mm. From this analysis shows that the structural strength of the package air conditioner’s holder is still in safe condition.